Activity Based Costing (ABC) Method Dalam Menentukan Tarif Layanan Rawat Inap pada RSUD Provinsi NTB - Saputri, Depiana; Animah; Astuti, Widia (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to calculate and compare inpatient service rates at the RSUD Provinsi NTB using the Activity Based Costing (ABC) method and the rates established under Peraturan Gubernur No. 48 of 2015. The type of research employed is field research using a descriptive analysis method with a quantitative approach. The results indicate that there is a difference between the inpatient service rates calculated using the ABC method and those currently applied by the hospital. The ABC method produces rates that more accurately reflect the actual consumption of resources by each class of inpatient care. Therefore, the ABC method can serve as a more appropriate alternative for determining hospital service rates to achieve greater cost efficiency and transparency.